2011
DOI: 10.1159/000323916
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Porcine Colonic Epithelial Cells Grown in Primary Culture

Abstract: Background: Primary cultures of epithelial cells are suitable models for studying epithelial function and, in particular, the regulation of epithelial tightness in vitro. The aim of our study was to develop a protocol for the isolation and culture of porcine colonic epithelial cells and to establish transepithelial electrical resistance (TEER) as a functional parameter for epithelial tightness. Methods: Epithelial cells were obtained from the proximal colon of piglets by enzymatic dispase digestion. Cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…Based on these findings, it can be concluded that treatment with exogenous cholinergic agonists, mimicking ACh release by cholinergic enteric neurons, influences TJ assembly rather than cell proliferation. This interpretation is further supported by findings from a recent study showing that the TEER value of a cultured colonocyte layer depends directly on the extent of TJ formation [Petto et al, 2011]. The action of the cholinergic agonist carbachol may be mediated by two classes of AChR [Tapper et al, 1978]: the G-protein-coupled mAChR and the nAChR, which are members of a superfamily of ligand-gated ion channel receptors.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Based on these findings, it can be concluded that treatment with exogenous cholinergic agonists, mimicking ACh release by cholinergic enteric neurons, influences TJ assembly rather than cell proliferation. This interpretation is further supported by findings from a recent study showing that the TEER value of a cultured colonocyte layer depends directly on the extent of TJ formation [Petto et al, 2011]. The action of the cholinergic agonist carbachol may be mediated by two classes of AChR [Tapper et al, 1978]: the G-protein-coupled mAChR and the nAChR, which are members of a superfamily of ligand-gated ion channel receptors.…”
Section: Discussionmentioning
confidence: 58%
“…To elucidate the long-term response of epithelial cells to cholinergic stimulation, a cell culture model free of systemic influences and the neuronal components of the enteric nervous system was employed according to a published protocol [Petto et al, 2011]. The mRNAs for ZO-1 and occludin were detected in the cultured epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-established protocols are available for the isolation and cultivation of intestinal epithelial cells derived from different species that maintain the characteristics of the original cells [Golaz et al, 2007;Kaushik et al, 2008;Petto et al, 2011;Ren et al, 2011]. Nevertheless, the use of primary cultures is limited by small proliferative life spans that precede permanent growth arrest, termed "in vitro cellular senescence" [Hayflick, 1965[Hayflick, , 1985Kuilman et al, 2010;Rodier and Campisi, 2011].…”
Section: Introductionmentioning
confidence: 99%